STRATEGI ADAPTASI PEDAGANG KAKI LIMA DALAM MENGHADAPI PERUBAHAN EKONOMI KOTA X - Elisa Wulandari (PT. Habe Cendekia Utama, 2025)
Cirebon City's economy is primarily dominated by the manufacturing, trade, hotels and restaurants, transportation, communications, and services sectors. The city plays a strategic role in the Ciayumajakuning region and is a center of trade and business due to its strategic location on the north coast of Java. This study aims to identify and analyze the adaptation strategies of street vendors, enrich studies of economic sociology and informal entrepreneurship, and provide valuable input for the city government and street vendor associations. This research method uses a qualitative descriptive approach to explore the social and economic issues faced by street vendors in Cirebon City. Street vendors (PKL) in Cirebon City are an important part of the local economy, despite facing challenges such as rising raw material prices, government regulations, illegal levies, and competition from modern businesses. They operate flexibly, focusing on specialty foods and beverages, and employ adaptive strategies such as price adjustments, product diversification, and social media marketing to maintain competitiveness.